Psychoedu-Fitrah to Prevent Deviations of Santri's Sexual Orientation - Siti Mumun Muniroh (Islamic Studies Journal for Social Transformation, 2022)
This study aims to develop, test and analyze the effectiveness of spiritual psychological models to prevent students' sexual orientation deviations in Islamic boarding schools. The method used in this study is the ADDIE research and development model, with a mechanism for the stages of model development including Analysis, Design, Development or Production, Implementation or Delivery, and Evaluations. This study succeeded in revealing and concluding that there are several steps in carrying out psyched-nature procedures to prevent sexual behavior deviations, namely understanding adolescent sexual nature, training adolescent sexual natural skills, and training the actualization of adolescent sexual nature. Based on the assistance among students, it shows that psychoedu-fitrah has proven effective and can significantly prevent sexual orientation deviations for young students. Evidence of effectiveness is shown by a significance value reaching 0.000 (<0.05), with a t-value of -8,718.